Pengaruh diet dengan pengaturan indeks glikemik dan beban glikemik terhadap kadar glukosa darah atlet sepak bola remaja - Siwi, Tabita Prawita; Dieny, Fillah Fithra; Fitranti, Deny Yudi (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : Stability of blood glucose level is the important key of football match. Low Glycemic Load (GL) foods can decrease the metabolism change during postprandial time and during exercise. Objective : The purpose of this study was to know the effect ofÂ  diet with arrangement Glycemic Index (GI) and GL on blood glucose level in young football athletes.Methods : Quasi experimental study on 21 male football athletes aged 14-18 years old at Pusat Pendidikan dan Latihan Pelajar (PPLP) Jawa Tengah. Subjects were divided into three groups : High GI with High GL diet (H-H) with GI=70 GL=47, Low GI with High GL diet (L-H) with GI=35 GL=22, and Low GI with Low GL diet (L-L) with GI=34 GL=6. Subjects fasted before intervention. Data collected were VO2max and body fat percentage, blood glucose level one hour after intervention (BGL 1), blood glucose level two hour after intervention (BGL 2), and blood glucose level after running exercised with distance 2.4 km (BGL 3). Bivariate analysis used Kruskall Wallis test.Results : All of groups have same characteristics of age, body fat precentage, and VO2max. There were significant effect of diet with arrangement GI and GL on BGL 1 and BGL 2 (p<0.05), there was no effect of diet with arrangement GI and GL on BGL 3 (p>0.05).Conclusion : Diets with arrangement Glycemic Index and Glycemic Load affected blood glucose level one hour and two hour after intervention. The increases of blood glucose level occured significantly in group that given low Glycemic Index and low Glycemic Load diet.